Mission and the Bottom Line : Performance Incentives in a Multi-Goal Organization - Gine, Xavier; Mansuri, Ghazala; Shrestha, Slesh A. (World Bank, Washington, DC, 2017)
The impact of performance pay in institutions with multiple goals depends on complementarities in the disutility cost of effort and how different tasks interact to achieve each goal. Workers of a mission-oriented nonprofit were randomly assigned to one of two bonus schemes, each incentivizing one of its two main operational goals: the performance of its microcredit program and the strengthening of community institutions of the poor. This study finds that the credit bonus improved credit-related outcomes but it undermined the social outcome. In contrast, the social bonus advanced the social mission as well as the microcredit program, but only for employees working alone, undermining the performance of employees working in teams. These results cannot be explained by a standard multitask principal-agent model featuring only complementarities in the disutility cost of effort. Instead, they suggest that production complementarities are also relevant.